2010
DOI: 10.3310/hta14550-04
|View full text |Cite
|
Sign up to set email alerts
|

A randomised, partially observer blind, multicentre, head-to-head comparison of a two-dose regimen of Baxter and GlaxoSmithKline H1N1 pandemic vaccines, administered 21 days apart

Abstract: A randomised, partially observer-blind, multicentre, head-to-head comparison of a two-dose regimen of Baxter and GlaxoSmithKline H1N1 pandemic vaccines, administered 21 days apart KG Participants: Three hundred and forty-seven subjects were identified and randomised to AS03 A -adjuvanted split-virion H1N1 vaccine or whole-virion (WV) vaccine in age groups [≥ 18-44 years (n = 140), ≥ 45-64 years (n = 136) and ≥ 65 years (n = 71)]. Interventions: Vaccine was administered by intramuscular injection into the del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 72 publications
1
5
1
Order By: Relevance
“…Contrary to the observations made by Nicholson et al using a similar vaccine in adults including the elderly, 20 no age-related declined immunological response was observed at Day 42 in the present study, and the data indicated that the immunological response was persistent up to Month 6 in both age strata (20–40 and 41–64 y). The safety profile of the vaccine in Asian adults was comparable to previous reports and no-Asia-specific safety concerns were reported.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to the observations made by Nicholson et al using a similar vaccine in adults including the elderly, 20 no age-related declined immunological response was observed at Day 42 in the present study, and the data indicated that the immunological response was persistent up to Month 6 in both age strata (20–40 and 41–64 y). The safety profile of the vaccine in Asian adults was comparable to previous reports and no-Asia-specific safety concerns were reported.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, a large proportion of the participants were found to have protective levels of antibodies against the vaccine strain even six months after vaccination with two doses (although age-related decline was evident), indicating that pandemic influenza vaccines can potentially confer immunity against successive waves of the same virus 20 . This is in agreement with previous studies using the AS03-adjuvanted H1N1 2009 vaccine that have demonstrated substantial benefits in terms of induction of rapid, strong and long-lasting immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Reporting bias is a major threat to the validity of results of conventional systematic reviews or MAs [4,5]. Accounting for reporting biases in NMA is challenging, because unequal availability of findings across the network of evidence may jeopardize NMA validity [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it was recommended for use by Health Canada in order to optimize vaccine efficacy and distribution in the Canadian population [4]. Immunogenicity of vaccine antigens is enhanced by inflammation [5-7] and clinical trial data indicates an increased incidence of non-severe vaccine-associated adverse events following administration of the ASO3 adjuvanted A/California/07/2009 H1N1 vaccine (Arepanrix TM ) compared to non-adjuvanted influenza antigen formulations [1,3,7]. These reported events were mainly symptoms of localized and systemic inflammation.…”
Section: Introductionmentioning
confidence: 99%